2007
DOI: 10.1017/s1368980007222931
|View full text |Cite
|
Sign up to set email alerts
|

Dietary transition stages based on eating patterns and diet quality among Haitians of Montreal, Canada

Abstract: Objectives: To identify dietary transition stages based on dietary patterns of adult Haitians having lived in Montreal for various lengths of time, and to assess associated dietary quality. Subjects: One hundred and eighty-one Haitians aged 25 -60 years were recruited by the modified random digit dialling method. Design: Socio-economic, diet and lifestyle variables were documented by questionnaire. Three non-consecutive 24-hour dietary recalls were conducted over a 3-month period. Dietary patterns were studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
52
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 42 publications
6
52
0
1
Order By: Relevance
“…Further, our findings are in accordance with several studies that have shown 'Western'-type dietary patterns to be followed more by younger individuals (30,(46)(47)(48)(49) . This may reflect acculturation to Western and/or urbanized eating habits and departure from traditional dietary habits (50) to a more modern and convenient dietary pattern mainly by younger generations.…”
Section: Discussionsupporting
confidence: 93%
“…Further, our findings are in accordance with several studies that have shown 'Western'-type dietary patterns to be followed more by younger individuals (30,(46)(47)(48)(49) . This may reflect acculturation to Western and/or urbanized eating habits and departure from traditional dietary habits (50) to a more modern and convenient dietary pattern mainly by younger generations.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings indicate that the notion of a turning point in food trajectories provides a useful conceptual framework as it contributes to an understanding of the first period after migration as a specific phase in the process of dietary acculturation. Previous studies indicate that the dietary changes observed among immigrants tend to correspond to a process described as "dietary transition" (Desilets et al 2007), a progressive shift towards more Westernized and unhealthy dietary patterns (Popkin 2002). In the case of immigrants, dietary transition is an integral part of the process of acculturation (Desilets et al 2007 investigating if and how early experiences with food affect the development of dietary habits and the possible implications for health are recommended.…”
Section: Discussionmentioning
confidence: 99%
“…This figure does not include illegal immigrants, estimated to be 230,000 in 2008 (Terrazas 2010). Increased rates of CVD risk factors such as obesity, hypertension and diabetes, have been found for African, Caribbean and Black populations in the U.S. and UK, yet dietary changes with acculturation are lacking (Désilets et al 2006 (Buchanan et al 2010), many of whom live in proximity to our laboratory. Diet quality may vary for Haitian Americans based on the influence of the host culture (U.S.).…”
mentioning
confidence: 97%
“…Dietary quality and physical activity are influenced by culture; for immigrants the culture of origin and the new or host culture impact their health behavior (Lara et al 2005;Désilets et al 2006). These changes are a part of the larger process of acculturation, whereby ethnic groups adopt the cultural patterns (customs, language, beliefs) of the dominant/host group.…”
mentioning
confidence: 99%
See 1 more Smart Citation